2018
DOI: 10.1590/s1806-37562017000000056
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical pneumococcal vaccine coverage: analysis of serotypes isolated from inpatients at a tertiary care hospital

Abstract: If the patients in this sample had been previously vaccinated with PCV13 plus PPV23, theoretically, 50.8% of the cases of invasive pneumococcal disease that required hospital admission could potentially have been prevented. Invasive pneumococcal disease should be prevented by vaccination not only of children and the elderly but also of adults in their economically productive years, so as to reduce the socioeconomic costs, morbidity, and mortality still associated with the disease, especially in underdeveloped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
9
1
1
Order By: Relevance
“…Studies have reported that adult vaccination coverage rate (VCR) is still at a suboptimal level in various countries 12,13 , including Brazil 14,15 . This has been attributed to limited public awareness, misinformation, vaccine hesitancy, gaps in recommending vaccines during healthcare visits and vaccine costs 1,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that adult vaccination coverage rate (VCR) is still at a suboptimal level in various countries 12,13 , including Brazil 14,15 . This has been attributed to limited public awareness, misinformation, vaccine hesitancy, gaps in recommending vaccines during healthcare visits and vaccine costs 1,16 .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the JBP, Dullius et al 1 present the results of their study involving a population of adult patients with invasive pneumococcal disease (IPD). Although similar studies have been conducted in populations of pediatric patients and immunosuppressed patients, there have been few such studies involving adult populations.…”
mentioning
confidence: 99%
“…The study conducted by Dullius et al, 1 published in this issue of the JBP, brings us the knowledge of pneumococcus in one region of Brazil (the state of Rio Grande do Sul), as well as of the serotyping of isolates from patients with IPD. A series of cultures were collected over an 11-year period, and the pneumococcal serotypes were correlated with the clinical status recorded in medical records and with the mortality rates found.…”
mentioning
confidence: 99%
See 2 more Smart Citations